Modelos DSGE e a crise de 2008: o debate acerca de suas limitações estruturais - Dias, Édipo Tenório Holanda (2019)
The 2008 financial crisis was responsible for placing the DSGE models at the Center of the macroeconomic debate. Their unsatisfactory performance during the period of the crisis has prompted authors of the most varied theoretical bases to think about the subject. Heterodox and Orthodox authors made analyzes, criticized the models and presented proposals for the future of the development of macroeconomic modeling. A relevant issue is that this movement of authors occurs in a disorganized way. Positions are pulverized in various means of publication. There are interviews on websites, postings on personal blogs, documents directed to government bodies, articles in magazines, among others. This reality required the discussion about the DSGE models to be made in an organized way. In this context, this research aimed to make explicit the post-crisis debate about the structural limitations of DSGE models. For this, it was necessary, in the first place, the development of a timeline of the DSGE models, responsible for the theoretical understanding of their evolution.The next steps were the creation of taxonomies, both for model critiques and proposals for the future of the macroeconomics, to allow a better understanding of the stage of the debate. These taxonomies evidenced proximity and distance between the authors' positioning. They have shown that heterodox authors reaffirm their position on the mainstream economy and understand the need for it to be overcomed. In orthodoxy, there is some distinction of positions, but they did not indicate abrupt changes in the development of macroeconomic modeling. The DSGE models should remain, in the coming years, as an important tool among those available to Central Banks to carry out their economic policy management. It is given a highlight to the relative consensus between orthodox and heterodox authors, who showed concern with the financial sector and the modeling of this sector in the DSGE models. With different theoretical bases, the authors understood that this sector needs to be better understood so that new crises originating in the financial sector can be anticipated or mitigated, thus avoiding large fluctuations in the world economies. Some of the authors presented concrete proposals, alternative models, to minimize such concern. Others understood that the improvements should be implemented within DSGE modeling still.